Economic development in the tropics - Hodder, Bramwell William (London : New York Methuen, 1980)
The book provides a discussion of the resources of the tropics, covering topics like: natural resources like climate and water supply; human resources and the population problem, types of tropical, agriculture, industrialisation, transport, markets and trade; problems of industrialisation and raw material and case studies of Brazil, Nigeria and India.
Includes bibliographical references and index.
lje 20/09/2018
Loans
Keywords: Economic development; Economic policy; Economic conditions - tropics; Tropical regions; Developing countries